Microplastics in advanced biological wastewater treatment plant of Kocaeli, Turkey: point source of microplastics reaching Marmara Sea - Erkan, H. Sari; Emik, H. H.; Engin, G. Onkal (SPRINGER, 2023)
Urban wastewater treatment plants (WWTPs) are major contributors of microplastics (MPs) in the environment, despite achieving relatively high removal percentages. This study conducted a comprehensive assessment of the abundance and characteristics of MPs in wastewater and sludge at various treatment stages at Gebze WWTP located in the Marmara Sea, for the first time. The influent exhibited an average MPs concentration of 70.1 +/- 28.6 MPs/L. After undergoing the fine screen and grit chamber units, the MPs concentration significantly reduced to 19.7 +/- 3.6 MPs/L, indicating an impressive removal rate of 71.8%. Upon completion of the secondary treatment, the effluent contained 7.1 +/- 1.7 MPs/L, resulting in an overall MP removal of 89.9-91.0%. The findings indicated that fibers constituted the predominant particle shape, followed by fragments. Fibers were effectively removed through primary treatment (71.8%), while fragments were efficiently removed during secondary treatment (81.1%). The analysis of sludge samples from the aeration basin and sludge thickening tank revealed higher concentrations, with 14.3 and 25 folds increase compared to the influent, respectively indicating the accumulation of MPs in sludge. Despite the treatment process, it is noteworthy that the effluent still exhibited a significant abundance of fibers. Micro-Raman analysis identified polyethylene and polypropylene as the main polymer types present. Although the WWTP demonstrated a high overall removal rate, an estimated 1022.4 x 106 +/- 244.8 x 106 MPs/d were still being discharged with the effluent into the Marmara Sea. Recognizing the potential impact of MPs on marine organisms, measures, such as introduction of tertiary treatment processes, were taken to mitigate this issue.
Keywords: Microplastics; Pollution; Wastewater treatment plant; Effluent discharge; Marmara Sea; ACTIVATED-SLUDGE PROCESS; FATE; IDENTIFICATION; REMOVAL; PARTICLES; GLITTERS; FIBERS; Environmental Sciences & Ecology